EFFECT OF JH III AND β-ECDYSONE ON SEMINAL VESICLE PROTEIN SECRETION IN THE TROPICAL TASAR SILKMOTH, ANTHERAEA MYLITTA (DRURY) (LEPIDOPTERA: SATURNIIDAE) - V. R. PENDAM,; D. B. TEMBHARE, (The Bioscan, 2013)
The present studies revealed an active secretory activity in the seminal vesicles soon after emergence of the male tasar silkmoth, Antheraea mylitta. The total concentration of DNA, RNA and proteins in the seminal vesicle tissue showed gradual reduction with advancement of age of the male moth. The SDS-PAGE analyzed about 11 protein bands ranging from 31.8 to 196.1 in molecular weight. Topical application of juvenile hormone (JH-III) on the newly emerged adult male moths showed enhancement while that of β-ecdysone (βE) caused depletion of the total seminal vesicle protein concentration.